Trends in Statutory Interpretation and the Judicial Process - Tokeley, Kate (Victoria University of Wellington Law Review, 2002)
The author presents a commentary regarding trends in statutory interpretation. In the first half of this article, the author explores a shift from strict literal statutory interpretation to the natural and ordinary meaning in context. The purposive approach, reflected in section 5(1) of the Interpretation Act 1999, and the rights-based value-based interpretation, which shifts the power to create laws onto the judiciary, are also explored. The author concludes that it remains the case that words should only be given meanings which they are reasonably capable of bearing. The second half of this article argues that well-reasoned dissents are a valuable part of the legal process. The author notes that a dissent can express an opposing view to the majority without directing personal attacks on the majority judges. Dissents also allow the public to see that each judge has independently contributed their individual perspective to the decision-making process, thereby promoting public confidence. A dissenting judgment can also bolster a majority judgment by giving the opportunity to provide counterarguments. Finally, dissents reflect the idea that the law is not always objective and determinate as it can be affected by the unique perspectives of the individual members of the Court.